The origins of bubbles in laboratory asset markets - Lucy F. Ackert; Narat Charupat; Richard Deaves; Brian D. Kluger (Federal Reserve Bank of Atlanta, 2006)
In twelve sessions conducted in a typical bubble-generating experimental environment, we design a pair of assets that can detect both irrationality and speculative behavior. The specific form of irrationality we investigate is probability judgment error associated with low-probability, high-payoff outcomes. Independently, we test for speculation by comparing prices of identically paying assets in multiperiod versus single-period markets. When these tests indicate the presence of probability judgment error and speculation, bubbles are more likely to occur. This finding suggests that both factors are important bubble drivers.
Keywords: 330; Finanzmarkt; Spekulationsblase; Test